The Pakistan-China FTA: legal challenges and solutions for marine environmental protection - Khan, Asif; Ullah, Maseeh (Frontiers in Marine Science, 2024)
Marine ecosystems play a vital role in development, human life, and health, thereby promoting sustainable development. However, due to rapid industrialization and urbanization, as well as intense exploitation of marine resources, among other phenomena, both Pakistani and Chinese marine ecosystems face severe challenges such as pollution, overfishing, and habitat destruction. In particular, the Pakistan-China Free Trade Agreement, which aims to boost economic growth, exacerbates these environmental issues due to the increased trade volume. The purpose of this article is to discuss the challenges of legal standards regulating marine environmental protection within the context of the Pakistan-China Free Trade Agreement. By examining the current state of the mentioned agreement as well as regional judicial practice, the current study demonstrates the need to adopt a number of legal measures, such as including specific teeth provisions within the Free Trade Agreement, establishing a special joint environmental commission, increasing public participation, and boosting national environmental law, in order to reduce the adverse effect on marine ecosystems and properly mitigate such effects with a view to achieving sustainability.